Outcomes and Risk Based Supervision in Pensions : Methodology with a Case Study for Costa Rica - Price, William; Ashcroft, John; Inglis, Evan (World Bank, Washington, DC, 2016)
This report illustrates a new methodology to develop an Outcomes and Risk Based Supervision (ORBS) framework for funded pensions with a case study of Costa Rica. The approach was used in a FIRST1 funded project in Costa Rica with the regulator and supervisor of pensions SUPEN. The intention is to highlight an approach that may be useful in the region, and globally, to help agencies responsible for private pensions to focus on the long run outcomes they are seeking to achieve, identify the risks to these outcomes and implement the most effective solutions to these risks. This is all done through a consistent framework that embeds the long run outcomes at the heart of the process, and so lends itself naturally to the greater focus on results, and Monitoring and Evaluation that are central to modern development projects. The focus on Costa Rica also helps illustrate the approach in a country that has not typically been used as a case study. This helps to broaden the range of case studies available for practitioners and expands the possibilities for ‘South-South’ learning. It also shows how the approach can be tailored to the specific characteristics of a country. The report starts with a description of the Costa Rican pension system. This provides the context for the case study. It helps to illustrate the variety of defined benefit and defined contribution pensions that needed to be covered. It also identifies the wide range of different institutions involved in delivering good pension outcomes, and hence the ‘eco-system’ in which the supervisor needs to operate effectively to improve outcomes for the benefits of pension savers in Costa Rica.